Inhibition of Cu Underpotential Deposition on Au Nanoparticles: The Role of the Citrate Capping Agent and Nanoparticle Size - Plowman, B; Compton, R (2014)
Cu underpotential deposition (UPD) is compared between a Au macroelectrode and Au nanoparticles ranging between 1.8 nm and 123 nm in size in order to identify whether the capping agent or nanoparticle size affects this reaction. It was found that the surface coverage of Cu was markedly decreased in the presence of the citrate capping agent, while a strong size dependence was also observed, with nanoparticles smaller than 60 nm displaying significantly less defined Cu UPD responses. These results highlight the influence of both the capping agent and nanoparticle size for UPD applications, such as the electrochemical determination of surface areas and the formation of bimetallic surfaces.